Calibration of Herbicide Applicators - Jason A. Ferrell; Brent A. Sellers; Pratap Devkota (EDIS)
If pesticide applicator equipment is not properly calibrated, the pesticide will probably be applied below or above the desired application rate. This 3-page document discusses the two most common methods for sprayer calibration. Written by Jason A. Ferrell, Brent A. Sellers, and Pratap Devkota, and published by the UF/IFAS Agronomy Department, revised May 2020.